Thermo-electric simulation of battery-modules with reduced order modelling of linear electrical components. Issue 5 (4th September 2017) - Pichler, Franz; Koester, Niels; Thaler, Alexander
Abstract : Purpose: This paper aims to present a fully coupled thermo-electrical finite-element battery model with an applied model-order reduction. The model is used to analyse the thermal design of battery modules during typical drive-cycles of electric vehicles. Design/methodology/approach: A model-order reduction is applied, in which the electrical linear bus-bars are analysed in an a-priori step. For these bus-bars, special distributed basis-functions are computed, which make the solution of differential Ohm's law unnecessary during the transient simulation. Furthermore, the distributed basis-functions are used to strongly couple the non-linear battery models, which reduces the iterations needed to simulate them. Findings: Altogether, this results in a fast simulation scheme for coupled linear and non-linear electrical components and their thermal behaviour. Originality/value: The presented method delivers an innovative approach, on how to systematically minimize the computational effort in a system of linear and non-linear electrical components, while keeping the full three-dimensional information of the original problem.